Students' Ability to Write Pantun in Class V at Lampeudaya Elementary School, Aceh Besar - Firdausia, Rizka Firdausia; Nurmasyitah, Nurmasyitah; Yamin, M. (Universitas Syiah Kuala, 2023)
The purpose of this study was to describe students' ability to write rhymes in class V at SD Negeri Lampeudaya Aceh. This research method uses descriptive quantitative research methods while the research subjects are as many as 17 students. Data collection techniques carried out by researchers use performance assessment, observation, and documentation of pantun results. Based on the results of the study, there were 9 students (52.9%) who got the very good category, 6 students (35.2%) who got the good category, 2 students (11.7%) who got the moderate category. Students' ability to write rhymes is obtained with an average value of 89.24. And based on the results of observations there are some students who do not have a high curiosity about rhymes. Therefore, it can be concluded that the ability of students to write rhymes based on the assessment of performance results and observations in class V at SD Negeri Lampeudaya Aceh Besar is included in the very good category.The purpose of this study was to describe students' ability to write rhymes in class V at SD Negeri Lampeudaya Aceh. This research method uses descriptive quantitative research methods while the research subjects are as many as 17 students. Data collection techniques carried out by researchers use performance assessment, observation, and documentation of pantun results. Based on the results of the study, there were 9 students (52.9%) who got the very good category, 6 students (35.2%) who got the good category, 2 students (11.7%) who got the moderate category. Students' ability to write rhymes is obtained with an average value of 89.24. And based on the results of observations there are some students who do not have a high curiosity about rhymes. Therefore, it can be concluded that the ability of students to write rhymes based on the assessment of performance results and observations in class V at SD Negeri Lampeudaya Aceh Besar is included in the very good category.